Quality of life on the views of older family carers of people with dementia - Oliveira, Deborah; Vass, Catherine D.; Aubeeluck, Aimee (SAGE, 2017)
Older family carers of people with dementia represent an increasing but overlooked population of family carers. This research aimed to explore how these individuals make sense of their own quality of life and to identify the factors that enhance or compromise this. Four focus groups were conducted in 2014 with 19 older family carers in community-based support groups in Nottinghamshire, United Kingdom. Data was transcribed verbatim and analysed using Interpretative Phenomenological Analysis. Thirty-three subthemes emerged and were collated into three superordinate themes: 1) aspects of care and caregiving, 2) feelings and concerns, and 3) satisfaction with life and caregiving. This study identified a broad range of aspects that are of particular importance to the QoL of older family carers of people with dementia. These findings are expected to inform future research as well as health and social care providers with the aim of improving life quality for this population.